Empathy for Nature: Reflections on socially engaged arts - (:unkn) unknown (My University, 2023)
In a world where the climate-change crisis demands urgent attention, socially engaged art interventions stand as a testament to the artist’s commitment to not onlycapturingthevalueofourpresenceinthephysical world but also actively participating in conversations that inspire environmental care. The interventions presented here transcend traditional artistic boundaries, compelling viewers to consider their relationship with nature in novel and thought-provoking ways. Together, these accomplishments underscore the transformative power of socially engaged art interventions, fostering community participation, and propelling critical discussions about the cultivation of an empathetic stance towards nature and non-human beings.
Keywords: Empathy; Visual arts; Socially engaged arts